Phospho-mimetic CD3ε variants prevent TCR and CAR signaling - Woessner, Nadine M.; Brandl, Simon M.; Hartmann, Sara; Schamel, Wolfgang W.; Hartl, Frederike A.; Minguet, Susana (Frontiers in Immunology, 2024)
Antigen binding to the T cell antigen receptor (TCR) leads to the phosphorylation of the immunoreceptor tyrosine-based activation motifs (ITAMs) of the CD3 complex, and thereby to T cell activation. The CD3ε subunit plays a unique role in TCR activation by recruiting the kinase LCK and the adaptor protein NCK prior to ITAM phosphorylation. Here, we aimed to investigate how phosphorylation of the individual CD3ε ITAM tyrosines impacts the CD3ε signalosome. Therefore, we mimicked irreversible tyrosine phosphorylation by substituting glutamic acid for the tyrosine residues in the CD3ε ITAM. Integrating CD3ε phospho-mimetic variants into the complete TCR-CD3 complex resulted in reduced TCR signal transduction, which was partially compensated by the involvement of the other TCR-CD3 ITAMs. By using novel CD3ε phospho-mimetic Chimeric Antigen Receptor (CAR) variants, we avoided any compensatory effects of other ITAMs in the TCR-CD3 complex. We demonstrated that irreversible CD3ε phosphorylation prevented signal transduction upon CAR engagement. Mechanistically, we demonstrated that glutamic acid substitution at the N-terminal tyrosine residue of the CD3ε ITAM (Y39E) significantly reduces NCK binding to the TCR. In contrast, mutation at the C-terminal tyrosine of the CD3ε ITAM (Y50E) abolished LCK recruitment to the TCR, while increasing NCK binding. Double mutation at the C- and N-terminal tyrosine (Y39/50E) allowed ZAP70 to bind, but reduced the interaction with LCK and NCK. Overall, the data demonstrate that the dynamic phosphorylation of the CD3ε ITAM tyrosines is essential for CD3ε to orchestrate optimal TCR and CAR signalling and highlights the key role of CD3ε signalosome to tune signal transduction.